Pengaruh Thin Capitalization, Koneksi Politik dan Risiko Perusahaan terhadap Penghindaran Pajak dengan Biaya Audit sebagai Variabel Moderasi (Studi Kasus pada Perusahaan Sektor Barang Konsumsi Primer yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2023) - Harahap, Safrina Fania Asyha (Tauhidinomics: Journal of Islamic Banking and Economics, 2025)
Indonesia’s low tax ratio remains a key challenge, especially in sectors like palm oil where unpaid taxes persist. Despite the growing number of companies, tax revenue hasn’t kept pace. This study examines the effects of thin capitalization, political connections, and firm risk on tax avoidance, with audit fees as a moderating variable. Using Moderated Regression Analysis (MRA) with EViews 13 and a quantitative panel data approach, the study analyzes 144 samples from 125 consumer non-cyclicals companies listed on the Indonesia Stock Exchange between 2019–2023. Based on agency theory, the findings indicate that thin capitalization significantly increases tax avoidance as debt rises. In contrast, political connections and firm risk show no direct significant effect. However, audit fees play a moderating role, reducing the impact of firm risk on tax avoidance.